Establishment of a Captive Cave Nectar Bat ( Eonycteris spelaea ) Breeding Colony in Singapore - Foo, Randy; Hey, Ying Ying; Jia Ng, Justin Han; Chionh, Yok Teng; Chia, Wan Ni; Kong, Pui San; Lee, Benjamin P Y-H; Kang, Adrian Eng Zheng; Borthwick, Sophie Alison; Low, Dolyce Hong Wen; Mendenhall, Ian Hewitt; Macabe Pena, Edgar; et al. (Journal of the American Association for Laboratory Animal Science, 2022)
Bats are known natural reservoirs of several highly pathogenic zoonotic viruses, including Hendra virus, Nipah virus, rabies virus, SARS-like coronaviruses, and suspected ancestral reservoirs of SARS-CoV-2 responsible for the ongoing COVID-19 pandemic. The capacity to survive infections of highly pathogenic agents without severe disease, together with many other unique features, makes bats an ideal animal model for studying the regulation of infection, cancer, and longevity, which is likely to translate into human health outcomes. A key factor that limits bat research is lack of breeding bat colonies. To address this need, a captive bat colony was established in Singapore from 19 wild-caught local cave nectar bats. The bats were screened for specific pathogens before the start of captive breeding. Custom-made cages and an optimized diet inclusive of Wombaroo dietary formula, liquid diet, and supplement of fruits enabled the bats to breed prolifically in our facility. Cages are washed daily and disinfected once every fortnight. Bats are observed daily to detect any sick bat or abnormal behavior. In addition, bats undergo a thorough health check once every 3 to 4 mo to check on their overall wellbeing, perform sampling, and document any potential pregnancy. The current colony houses over 80 bats that are successfully breeding, providing a valuable resource for research in Singapore and overseas.